Innovative strategies to reduce traffic related injuries and deaths in youth - Joanne Banfield (19794507) (2015)
Road traffic injuries are the leading cause of death among young people, aged 15-29 years (1). It is generally accepted that the high rate of adolescent injuries may be due to a variety of factors. Studies have shown young drivers are more likely to underestimate the probability of specific risks caused by traffic situations, as well as to overestimate their own driving skills making them more vulnerable to trauma. It has also been hypothesized that adolescents are more prone to motor vehicle collisions due to their risk-taking attitudes (2). There is consensus among experts in the field of road safety that the best road safety strategies and programs are based on research-driven and psycho-social theories of behavior (3). The P.A.R.T.Y. (Prevent Alcohol and Risk-Related Trauma in Youth) Program is one of those programs. Developed in 1986, P.A.R.T.Y. is a one day, in hospital injury awareness and prevention program for youth aged 15 and older. The goal is to provide young people with information about trauma that will enable them to recognize their injury risks, make prevention-oriented choices and adopt behaviours that minimize unnecessary risks through vivid clinical reality. Attitudes towards risk taking in traffic have been correlated with aggressive driving behavior, speeding, and intention to commit traffic law violations. Thus, an effective intervention to increase road safety may be to change the attitudes that influence the driving behavior of adolescents. This is consistent with the cognitive dissonance theory, which states that changing the beliefs that underlie certain behaviors can cause a behavioral change (2). From these theories, one can expect that changing the risk taking attitudes of adolescents can lead to a decrease in the probability of collisions. A recent meta-analysis suggested interventions aimed at influencing attitudes might be the most effective measure to improve safety on the roads (2). Other Information Published in: Journal of Local and Global Health Science, title discontinued as of (2017) License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.5339/jlghs.2015.itma.72